Conflict and Displacement: The Life Stories of Internally Displaced Families (IDFs) - Teves, Mary Melmar G. (Jurnal Ilmiah Peuradeun, 2024)
Internal displacement is a global phenomenon that generates massive effects on humanity. The Philippines is one country prone to internal displacement, ranging from natural causes to conflict-induced displacement. The armed conflict that transpired in an urban city in Mindanao, Philippines, produced unimaginable outcomes for the lives of internally displaced families (IDFs). Thus, exploring their experiences yields a broader grasp of internal displacement. Since the topic of internal displacement is intermittently concentrated, the study could provide supplementary literature in the field of social sciences, particularly in studying displacement. The study utilized phenomenological inquiry to delve into the lived experiences and coping mechanisms of the IDFs during their displacement. Through Colaizzi’s thematic analysis, findings were depicted in six (6) emergent themes. As to the participants’ experiences, the themes were: Terror Brings Deep Stress, Inhumanity of War, and Displacement in Laden with Adversities. The themes detailed the inhumane repercussions of conflict-induced displacement. Nevertheless, the IDFs remarkably subdued these adversities through their coping mechanisms, which were thematically described as Patience Beats Obstacles, Positivity Survives Difficulty, and Tightened Faith.